Continuous Quality Improvement and Comprehensive Primary Health Care: A Systems Framework to Improve Service Quality and Health Outcomes - McCalman, Janya; Bailie, Ross; Bainbridge, Roxanne; McPhail-Bell, Karen; Percival, Nikki; Askew, Deborah; Fagan, Ruth; Tsey, Komla (Frontiers in Public Health, 2018)
Continuous quality improvement (CQI) processes for improving clinical care and health outcomes have been implemented by primary healthcare services, with resultant healthcare impacts. But only 10% to 20% of gain in health outcomes is contributed by healthcare services; a much larger share is determined by social and cultural factors. This perspective paper argues that healthcare and health outcomes can be enhanced through applying CQI as a systems approach to comprehensive primary healthcare. Referring to the Aboriginal and Torres Strait Islander Australian context as an example, the authors provide a systems framework that includes strategies and conditions to facilitate evidence-based and locally-responsive decision making by primary healthcare services. The framework describes the integration of CQI vertically to improve linkages with governments and community members, and horizontally with other sectors to influence the social and cultural determinants of health. Further government and primary healthcare service investment is required to support and extend integration and evaluation of CQI efforts vertically and horizontally.